Early Mortality in Patients who Received Extensive Surgical Management for Acute Type A Aortic Dissection - Analysis of 452 Consecutive Cases from a Single-center Experience - Abdelhameed,Ahmed Sayed (2020)
Abstract Objective: To detect the potential risk factors associated with early mortality in patients who received extensive surgical management, in the form of total arch replacement plus frozen elephant trunk and arch debranching (hybrid repair technique), for acute type A aortic dissection. Methods: The clinical and surgical data of 452 surgically treated patients with acute type A aortic dissection at our center, between March 2010 and December 2016, have been retrieved. Uni and multivariate logistic regression analyses were carried out to detect the effect of various preoperative demographics and different perioperative variables on early mortality. Results: Overall 30-day mortality occurred in 70 out of 452 patients (15.4%). The principal causes of death were multiple organ failure (n=38), cardiac failure (n=18), and severe pulmonary infection (n=10). Risk factors for early mortality were identified with multivariate analysis. Preoperatively, overweight (P<0.025), alcohol drinking (P<0.002), coronary artery disease (P<0.014), hemodynamic shock (P<0.006), and elevated white blood cells count (P<0.002) were associated with higher mortality rate. Postoperatively, prolonged operation time (P<0.008), stroke (P<0.0001), and acute renal dysfunction (P<0.0001) were highly associated with death. Conclusion: Considering the advantages of extensive surgical management for acute type A aortic dissection over the other less aggressive surgical approaches, it should be advised whenever indicated, provided that being carried out by experts in the field of adult aortic surgery in high-volume centers. The surgeon should be aware of the patient’s preoperative comorbidities and other risk factors for early mortality, in particular, prolonged operation time.